Optimization Study on Incremental Forming of Sheet Metal AA5052 for Variable Wall Angle using CNC Milling Machine. (2018) - Pandivelan, C.; Jeevanantham, A.K.; Sathiyanarayanan, C.
Abstract: Single Point Incremental Forming (SPIF) of sheet metals is a novel manufacturing method to accomplish the increasing demand in manufacturing industries and sheet metal based new product development. It is a pioneering and economically feasible alternative to the stamping process in manufacturing and rapid prototyping of sheet metal parts in small batches. This process requires a CNC machine, simple spherical ended tool and a simple setup for holding the sheet metal. This paper investigates and enlights the formability of AA 5052 sheets by the effect of various parameters like feed rate, rotational speed of the tool (RPM), vertical step down, and diameter of the tool. Taguchi's L9 orthogonal array based design of experiments was conducted and favorable combination of parameters was identified to enhance the formability in terms of wall angle test.